Vertical performance of suction bucket foundation for offshore wind turbines in sand. (15th May 2019) - Wang, Xuefei; Zeng, Xiangwu; Li, Jiale
Abstract: The suction bucket foundation is turning to be an increasingly prevalent foundation for offshore wind turbines (OWTs). In this study, a series of centrifuge tests are performed to investigate the vertical bearing capacity of the suction bucket foundation in sandy soil under drained condition. Four bucket models are tested by considering the influence of aspect ratios (APs). The foundations are tested under compressive and tensile vertical loadings. The bucket foundation is in the general shear failure mode, and the ultimate bearing capacity increases with the AP. The tensile bearing capacity is smaller than the compressive capacity. The sharing factor of the base capacity and the skirt friction of the suction bucket foundation is determined with the assistance of the tensile test. The bucket lid provides the majority of the bearing capacity. The internal skirt friction is larger than the external skirt friction due to the soil constraint effect and the increased vertical stress. Several analytical methods are proposed to estimate the bearing capacity, and the results are compared with the test data. The bearing capacity equation is more applicable to the "wide-shallow" bucket foundations. The recommended design method is regarded as the upper bound when calculating the ultimate bearing capacity.